Xiaoyaosan Decoction, a Traditional Chinese Medicine, Inhibits Oxidative-Stress-Induced Hippocampus Neuron Apoptosis In Vitro. (29th January 2012) - Meng, Zhen-zhi; Hu, Jing-hong; Chen, Jia-xu; Yue, Guang-xin
Abstract : Xiaoyaosan (XYS) decoction is a famous prescription for the treatment of mental disorders in China. In this experiment, we explored the way in which XYS decoction-reverse hippocampus neuron apoptosis in vitro. We used XYS decoction-containing serum to treat oxidative-stress-induced hippocampus neuron apoptosis and used immunofluorescence to determine the concentration of free calcium, mitochondrial membrane potential, and apoptotic rate of neuron. Results showed that 3-hour oxidative stress decrease mitochondrial membrane potential, increase the concentration of free calcium and apoptotic rate of neuron via triggering pathological changes of nucleus such as karyorrhexis, karyopyknosis. Low, medium, high dose of XYS-decoction-containing serum could reverse these phenomenon, and the effect of low-dose XYS-decoction-containing serum was significant in improving mitochondrial membrane potential and apoptotic rate of neuron. These findings suggest that XYS decoction may be helpful in reducing oxidative-stress-induced hippocampus neuron apoptosis.